2012
DOI: 10.1016/j.jde.2012.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Analytic well-posedness of periodic gKdV

Abstract: In the periodic case, it is proved that the Cauchy problem for the generalized Korteweg-de Vries equation (gKdV) is locally well-posed in a class of analytic functions that can be extended holomorphically in a symmetric strip of the complex plane around the x-axis. Thus, the uniform analyticity radius of the solution does not change as time progresses. Also, information about the regularity of the solution in the time variable is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…For large times on the other hand we use the idea introduced in [17] (see also [16]) to show that σ(t ) can decay no faster than 1/|t | as |t | → ∞. For studies on related issues for nonlinear partial differential equations see for instance [2,3,10,11,12,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…For large times on the other hand we use the idea introduced in [17] (see also [16]) to show that σ(t ) can decay no faster than 1/|t | as |t | → ∞. For studies on related issues for nonlinear partial differential equations see for instance [2,3,10,11,12,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…This question has received some attention in the case of the KdV equation and its generalizations. For short times, it is known that the radius of analyticity remains at least as large as the initial radius; see Grujić and Kalisch [6] for the non-periodic case, and also Li [15], Himonas and Petronilho [8], and Hannah, Himonas and Petronilho [7] for the periodic case. For the global problem, the non-periodic case was studied by Bona, Grujić and Kalisch in [2], where it was shown that the radius of analyticity for the KdV equation can decay no faster than t −12 as t → ∞ (see Theorem 4 and Corollary 2 in [2]).…”
Section: Introductionmentioning
confidence: 99%
“…Motivation for this type of study comes from the global analytic theory of nonlinear evolution PDE started with the paper by Kato and Masuda [28] and based on the proof of the existence of global analytic solutions in the space variables for the related Cauchy problem. After [28], many authors proved results of this type for several models as the (generalized) Korteweg-de Vries equation, the Euler equations, the Benjamin-Ono equation, the nonlinear Schrödinger equation, see for instance [5,8,20,21,22,23,24,25,26]. A parallel study in an elliptic setting devoted in particular to the analyticity of travelling waves has been developed in [6,10,11,13,14].…”
Section: Introductionmentioning
confidence: 99%